Poesia e Crônica em Cora Coralina - Andrade, Ludmila Santos (2016)
Known nationally as a poet, Cora Coralina started her life in literature with chronicle stories, using the journalism genre as a type of laboratory to perfect her writing, acquiring her own style. Only later she began writing in verses, through poems anchored in her experience, observation and memory. She incorporated her chronicle verve into her verses, and was always paying attention to the obscure and everyday life, in a way that her poems also constitute authentic chronicles, not only from Goiás, but from the Imperial Brazil, recently turned into a republic. From that, I propose in this paper to approach the work of Cora Coralina, with the purpose to bring to light her work in writing chronicles, as well as point out how the founding principles of the making of a chronicle are intrinsically and evidently connected to her poetic work. It is a documental and bibliographic research, made from the relation between the literary theories and her own literary text. In order to develop this research, the paper was structured into two chapters. In the first, with the goal of shedding light into how Cora Coralina practiced the genre of chronicles, we will look into the works Solidão, and Coisas de São Paulo, and lastly the poem Beco de Vila Rica, examining them to point out the different phases in her writing. In order to follow these phases, we collated these texts looking to evince the differences between her initial work and the work of her maturity, as well as the manner in which the poet incorporates into her poems the chronicle experience. In this chapter, we also indicate that the incursion of Cora Coralina into poetry is related to the readings that she had related to the Brazilian Modernismo movement. In order to examine how does Cora Coralina’s chronicle poetry relates to Modernismo, we observe the confluence between her work and that of other Brazilian poets from the same time, such as Manuel Bandeira and Mario Quintana. In the second chapter, we show that her poetry in intimately connected to the city of Goiás, and that it happens due to a process that chronicizes her city and her time. To make that analysis, we chose the poems: “Minha cidade”; “Moinho do tempo”; “Antiguidades”; “Escola de mestre Silvina” e “Coisas de Goiás: Maria”. From these poems we verified aspects such as the process of interweaving between the poet and the city, the record of historical facts and of the silent proceedings of the city of Goiás, as well as the educational methods, and still observe the approximation of her poetry to the small facts, representing the daily, the history and the inhabitants of Goiás. Therefore, we consider that the poems from Coralina make up true chronicles of the vilaboense society, the city of Goiás and the eccentric people from that city.